ANALYSIS DESIGN SYSTEM FOR PROSPECTIVE AIRCRAFT PASSENGERS IN NYIA AIRPORT - Rianto, Rianto; Aini S, Nanda Tri (Institut Teknologi Dirgantara Adisutjipto, 2021)
Air transportation is a necessity for regional economic activities, where passengers will have an important role for the survival of the aviation world. Knowing what factors are the most influential in the movement of prospective passengers is important to know the future of the aviation world, especially for the Special Region of Yogyakarta. So in this study designed a system that can be used to solve these problems. Where this system uses eight variables, namely the number of passengers, the number of residents, the number of hotels, the number of universities, the number of students, the number of hospitals, the number of workers, and the number of companies.